Cytokine Therapy Combined with Nanomaterials Participates in Cancer Immunotherapy - Heping Lian; Shuang Ma; Duoyi Zhao; Wei Zhao; Yan Cui; Yingqi Hua; Zhiyu Zhang (MDPI AG, 2022)
Immunotherapy has gradually become an emerging treatment modality for tumors after surgery, radiotherapy, and chemotherapy. Cytokine therapy is a promising treatment for cancer immunotherapy. Currently, there are many preclinical theoretical bases to support this treatment strategy and a variety of cytokines in clinical trials. When cytokines were applied to tumor immunotherapy, it was found that the efficacy was not satisfactory. As research on tumor immunity has deepened, the role of cytokines in the tumor microenvironment has been further explored. Meanwhile, the study of nanomaterials in drug delivery has been fully developed in the past 20 years. Researchers have begun to think about the possibility of combining cytokine therapy with nanomaterials. Herein, we briefly review various nano-delivery systems that can directly deliver cytokines or regulate the expression of cytokines in tumor cells for cancer immunotherapy. We further discussed the feasibility of the combination of various therapies. We looked forward to the main challenges, opportunities, and prospects of tumor immunotherapy with multiple cytokines and a nano-delivery system.